2011
DOI: 10.1371/journal.pone.0024166
|View full text |Cite
|
Sign up to set email alerts
|

Validation and Application of a PCR Primer Set to Quantify Fungal Communities in the Soil Environment by Real-Time Quantitative PCR

Abstract: Fungi constitute an important group in soil biological diversity and functioning. However, characterization and knowledge of fungal communities is hampered because few primer sets are available to quantify fungal abundance by real-time quantitative PCR (real-time Q-PCR). The aim in this study was to quantify fungal abundance in soils by incorporating, into a real-time Q-PCR using the SYBRGreen® method, a primer set already used to study the genetic structure of soil fungal communities. To satisfy the real-time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
106
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 211 publications
(109 citation statements)
references
References 63 publications
3
106
0
Order By: Relevance
“…Concurrently, many studies have also suggested that soil fungal diversity is strongly dependent on soil properties (Prevost‐Boure et al. 2011; Siciliano et al. 2014; LeBlanc et al.…”
Section: Introductionmentioning
confidence: 99%
“…Concurrently, many studies have also suggested that soil fungal diversity is strongly dependent on soil properties (Prevost‐Boure et al. 2011; Siciliano et al. 2014; LeBlanc et al.…”
Section: Introductionmentioning
confidence: 99%
“…To build the standard curves we used as templates the purified PCR products of known concentrations of the following pure cultures: Fusarium solani (DSMZ 10696), fungi, and Azospirillum irakense (DSMZ 11586), nifH gene. The primer pairs were FF390/FR1 (fungi; Prévost-Bouré et al 2011) and nifHf/nifHr (nifH gene; Töwe et al 2010). Stock concentration (gene copies µL −1 ) was determined via PicoGreen measurement and was freshly prepared for each run.…”
Section: Dna Extractionmentioning
confidence: 99%
“…Genetic approaches also provide additional information such as pathogenicity, especially if the genes targeted are those associated with the disease-causing abilities of the organism (Pathak et al, 2012). As a result, qPCR has been used to enumerate bacteria in different sample types, including food (Elizaquível et al, 2012), soil (Prévost-Bouré et al, 2011), wastewater (Sidhu et al, 2013 and marine sediments (Luna et al, 2012;Schippers et al, 2012). Despite these numerous applications, the use of qPCR in riverbed sediment studies is still in its early stages.…”
Section: Total Bacterial Dna Extractionmentioning
confidence: 99%